Randomized phase III trial of a neoadjuvant regimen of four cycles of adriamycin plus cyclophosphamide followed by four cycles of docetaxel (AC4-D4) versus a shorter treatment of three cycles of FEC followed by three cycles of docetaxel (FEC3-D3) in node-positive breast cancer (Neo-shorter; NCT02001506) - Hwang, Inhwan; Kim, Jeong Eun; Jeong, Jae Ho; Ahn, Jin-Hee; Jung, Kyung Hae; Son, Byung Ho; Kim, Hak Hee; Shin, Junyoung; Lee, Hee Jin; Gong, Gyungyub; Kim, Sung-Bae (Breast cancer research and treatment, 2023)
Purpose To determine whether six cycles of FEC3-D3 has a comparable efficacy to eight of AC4-D4. Methods The enrolled patients (pts) were clinically diagnosed with stage II or III breast cancer. The primary endpoint was a pathologic complete response (pCR), and the secondary endpoints were 3 year disease-free survival (3Y DFS), toxicities, and health-related quality of life (HRQoL). We calculated that 252 pts were needed in each treatment group to enable the detection of non-inferiority (non-inferiority margin of 10%). Results In terms of ITT analysis, 248 pts were finally enrolled. The 218 pts who completed the surgery were included in the current analysis. The baseline characteristics of these subjects were well balanced between the two arms. By ITT analysis, pCR was achieved in 15/121 (12.4%) pts in the FEC3-D3 arm and 18/126 (14.3%) in the AC4-D4 arm. With a median follow up of 64.1 months, the 3Y DFS was comparable between the two arms (75.8% in FEC3-D3 vs. 75.6% in AC4-D4). The most common adverse event (AE) was Grade 3/4 neutropenia, which arose in 27/126 (21.4%) AC4-D4 arm pts vs 23/121 (19.0%) FEC3-D3 arm cases. The primary HRQoL domains were similar between the two groups (FACT-B scores at baseline, P = 0.35; at the midpoint of NACT, P = 0.20; at the completion of NACT, P = 0.44). Conclusion Six cycles of FEC3-D3 could be an alternative to eight of AC4-D4. Trial registration ClinicalTrials.gov NCT02001506. Registered December 5,2013 . https://clinicaltrials.gov/ct2/show/NCT02001506